2016
DOI: 10.1021/acs.langmuir.6b02533
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Nanosized Aggregates of Fullerene C60 with Electrolytes in Methanol: Coagulation and Overcharging of Particles

Abstract: Contrary to numerous studies on the stability of fullerene aqueous colloidal solutions in the presence of electrolytes, the corresponding issue for the organosols was until recently almost unexplored. In this article, the state of C in methyl alcohol and the regularities of the coagulation of colloidal solution in this solvent were examined in the presence of electrolytes. Alcosols with a fullerene concentration of 4 × 10 M were prepared by the dilution of the C saturated solution in toluene by methanol. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 47 publications
5
30
0
Order By: Relevance
“…Our studies on C 70 and C 60 fullerenes demonstrated that the critical composition of the binary solvent, which corresponds to the appearance of colloidal aggregates, depends on the fullerene working concentration. 22,37 Therefore, some discrepancies are observed between the results by different authors. 34,36,37 In Figure 1, such a critical composition corresponds to 38 vol % toluene.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our studies on C 70 and C 60 fullerenes demonstrated that the critical composition of the binary solvent, which corresponds to the appearance of colloidal aggregates, depends on the fullerene working concentration. 22,37 Therefore, some discrepancies are observed between the results by different authors. 34,36,37 In Figure 1, such a critical composition corresponds to 38 vol % toluene.…”
Section: Resultsmentioning
confidence: 99%
“…Even for the most popular fullerene C 60 , such studies are few in number and probably originate only from this laboratory. 7,14,15 This is in stark contrast to the situation for aqueous suspensions and sols of fullerenes, for which coagulation via electrolytes has been studied in detail by many authors. 23−25 Meanwhile, besides elucidation of the stability conditions, such studies allow for evaluation of the Hamaker constant of the fullerene−fullerene interaction in vacuum.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations